Application of antibiotic bone cement combined with lobulated perforator flap based on descending branch of the lateral circumflex femoral artery in treatment of infected traumatic tissue defects of foot - Zhong-Bao Xu; Guo-Guang Dai; Zhong-Ye Sun; Hao Li; Jun Yan; Hai-Qing Li; Zhao-Qi Guo (BMC Musculoskeletal Disorders, 2024)
Abstract Objective To evaluate the clinical effectiveness of antibiotic bone cement combined with the lobulated perforator flap based on the descending branch of the lateral circumflex femoral artery (d-LCFA) in the treatment of infected traumatic tissue defects in the foot, in accordance with the Enhanced Recovery after Surgery (ERAS) concept. Methods From December 2019 to November 2022, 10 patients with infected traumatic tissue defects of the foot were treated with antibiotic bone cement combined with the d-LCFA lobulated perforator flap. The cohort comprised 6 males and 4 females, aged 21 to 67 years. Initial infection control was achieved through debridement and coverage with antibiotic bone cement, requiring one debridement in nine cases and two debridements in one case. Following infection control, the tissue defects were reconstructed utilizing the d-LCFA lobulated perforator flap, with the donor site closed primarily. The flap area ranged from 12 cm×6 cm to 31 cm×7 cm. Postoperative follow-up included evaluation of flap survival, donor site healing, and ambulatory function of the foot. Results The follow-up period ranged from 7 to 24 months, averaging 14 months. Infection control was achieved successfully in all cases. The flaps exhibited excellent survival rates and the donor site healed by first intention. Based on the American Orthopaedic Foot and Ankle Society (AOFAS) ankle-hindfoot scale, pain and function were evaluated as excellent in 3 cases, good in 5 cases, and moderate in 2 cases. Conclusion The application of antibiotic bone cement combined with the d-LCFA lobulated perforator flap is an effective treatment for infected traumatic tissue defects of the foot with the advantages of simplicity, high repeatability, and precise curative effects. The application of the d-LCFA lobulated perforator flap in wound repair causes minimal damage to the donor site, shortens hospital stays, lowers medical expenses, and accelerates patient rehabilitation, aligning with the ERAS concept. Therefore, it is a practice worth promoting in clinical use.